KEPASTIAN HUKUM BAGI KREDITUR DENGAN JAMINAN SERTIFIKAT HAK MILIK - Rosdiana Dewi, Elvira; Amalia, Lia; Abas, Muhamad (Collegium Studiosum Journal, 2024)
A practice that is widespread in banking, credit collateral is material in the form of land. In credit agreement practice, defaults often occur, therefore collateral is needed, so that credit agreements gain trust and have high economic value. In this writing, the author aims to find out the legal certainty of creditors regarding collateral in the form of property rights certificates in credit agreements and to find out what the judge's decision was in decision number 8/Pdt.G.S/2021/PN.Kwg. This research uses a normative juridical approach. This research concludes that in credit agreements with collateral, legal protection for creditors is very necessary. Therefore, material collateral is needed to minimize the risk of default by the debtor. Article 6 of the Mortgage Rights Law states that if there is a breach of contract in a credit agreement, the first mortgage holder has the right to sell the collateral that is the object of the mortgage through a public auction.